Overcoming the Socio-Economic Challenges to Good Governance: Streamlining Cooperative Governance Model - Bhekabantu Alson Ntshangase; Kaizer Raseane Makole; Steven Kayambazinthu Msosa (SocioEconomic Challenges)
The system of cooperative governance in the democratic South African dispensation was constitutionally mandated and institutionalised to improve intergovernmental relations that can streamline effective performance, implementation, and monitoring of government programmes to improve service delivery for citizens. However, despite numerous efforts and pleas by the Auditor-General of South Africa to responsible oversight structures like provincial governments and the Standing Committee on Public Accounts to curb financial malfeasance, corruption and lack of adequate and proper financial management skills, these pleas have fallen on deaf ears thus undermining cooperative and good governance mechanisms and systems. A practice of cadre deployment rather than meritocracy has become inherent when appointing and selecting local government officials and strategic thinkers who can be tasked to conceptualise new ideas of governance that can be associated with accountability and other good governance measures. The main question that this paper seeks to investigate is what causes poor governance and management performance in local municipalities under the African National Congress? The six themes generated from the analysis of literature reviews and strategic documents are meritocracy versus cadre deployment, strategic collaboration, human capital development, performance efficiency and efficacy, corruption and nepotism, and capital flight. Thus, to ensure best practices, parliamentary oversight structures and responsible departments, like the National Treasury, should build checks and balances in their institutional mechanisms that strive to streamline good cooperative governance practices and accountability measures as per constitutional prescripts to ensure that basic services are effectively and sufficiently rendered across cooperative governance spheres. Furthermore, appropriate oversight measures driven by political will from political superiors in the governing party should be adopted, inculcated, and institutionalised in the cooperative governance system of South Africa to punish serial offenders amongst accounting officers in local municipalities. This study is significant because it outlines effective oversight mechanisms that streamline good governance within the cooperative governance framework in the developing world with specific reference to South Africa.